Comparison of DNA Yield from Different Plant Materials of Plumeria sp. (Apocynaceae) - Martida, Vanesa; Pharmawati, Made (Advances in Tropical Biodiversity and Environmental Sciences; Vol 3 No 1 (2019): ATBES, 2019)
DNA extraction that gives good quantity and quality DNA is a basic step that must be completed for molecular studies, especially in DNA fingerprint imaging.  The aim of this research was to find out the better quality and quantity of DNA extracted from different plant materials of frangipani cultivars ( Plumeria sp.). Leaves and flowers were collected from Taman Jepun, Denpasar Bali.  Fresh young leaves and flowers were used as plant materials as well as dried leaves (silica gel dried leaves) of Plumeria sp.  This research used CTAB buffer with modification as lysis buffer.  Purification techique used NucleoSpin ® Gel and PCR Clean Up Kit. The results showed that the colour of DNA solution from fresh material was clear and the quantities of DNA from young fresh leaves were between 70-300 ng/µl. The DNA colour solution from flowers was also transparent with concentration between 0-40 ng/µl. DNA isolated from dry material resulted in brown solution with DNA quantity between 30-100 ng/µl and need to be purified to obtain clear DNA solution.